2012
DOI: 10.1155/2012/729283
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on Back and Core Muscular Endurance in Firefighters

Abstract: The purpose of this study was to assess the relationships between obesity and measures of back and core muscular endurance in firefighters. Methods. A cross-sectional study was conducted in career firefighters without low back pain. Obesity measures included body mass index (BMI) and body fat percentage assessed with air displacement plethysmography. Muscular endurance was assessed with the Modified Biering Sorensen (back) and Plank (core) tests. Relationships were explored using t-tests and regression analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 15 publications
2
27
0
2
Order By: Relevance
“…Although statistically significant gains were observed in back and core endurance in study participants, this suboptimal adherence may have tempered the potential benefits of exercise therapy 8. Given that firefighters have challenging physical demands, a high prevalence of obesity, generally low levels of physical activity, and a potential increased risk of cardiovascular disease, all of which may benefit from increased adherence to exercise therapy, it is important to understand barriers and facilitators to exercise in this population 1,9,14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although statistically significant gains were observed in back and core endurance in study participants, this suboptimal adherence may have tempered the potential benefits of exercise therapy 8. Given that firefighters have challenging physical demands, a high prevalence of obesity, generally low levels of physical activity, and a potential increased risk of cardiovascular disease, all of which may benefit from increased adherence to exercise therapy, it is important to understand barriers and facilitators to exercise in this population 1,9,14…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized controlled trial (RCT) reported that firefighters who participated in a 24-week supervised worksite exercise therapy program (note: the term “exercise therapy” is used to denote exercise that is prescribed for a specific therapeutic purpose rather than recreational exercise) had significantly improved back and core muscular endurance at 6 months compared with those who continued to do their usual physical fitness routine 8,9. However, adherence to the twice-weekly exercise therapy protocol over 24 weeks was suboptimal, as participants completed only 67.3% (mean 32.3) of the 48 sessions specified in the study protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to ageing, obesity triggers the infiltration of fat into muscle, which could be a cause of early development of sarcopenia as the intramuscular lipid droplets hinder the regeneration potential and function of skeletal muscle . Besides the muscular force, muscular endurance is negatively associated with BMI, which is also a characteristic of sarcopenia . Taken together, patients with obesity have been shown to have difficulty in performing activities of daily living and are more at risk of falls and fractures, common features of sarcopenia and ageing.…”
Section: Obesity and Age‐related Diseasesmentioning
confidence: 99%
“…[19] . Their augmented body weight increases muscular injury risks but also muscular endurance [20] . Therefore it is important for firefighters to keep fit by practicing the required exercises [21] .…”
Section: Discussionmentioning
confidence: 99%